Case-Finding tool for COPD in LMIC (COLA) - translation and cross-cultural adaptation into Brazilian Portuguese language - Kabbach, Erika Zavaglia; Leonardi, Naiara Tais; Siddharthan, Trishul; Borghi-Silva, Audrey; Alqahtani, Jaber Saud; Hurst, John R; Mendes, Renata Gonçalves (Revista de Saúde Pública, 2023)
OBJECTIVE: To translate and cross-culturally adapt the COPD in Low- and middle-income countries (LMICs) Assessment (COLA) questionnaire into Brazilian Portuguese, a case-finding instrument for chronic obstructive pulmonary disease (COPD). METHODS: Translation and cross-cultural adaptation were completed in six steps: the original version was translated into Brazilian Portuguese by two native speakers of the target language; the translated versions were synthesized; back-translation was performed by two native speakers of the original language; the back-translation and the Brazilian Portuguese version of the COLA were reviewed and harmonized by an expert committee of specialists; and, then, the pre-final version was tested by 30 health professionals who were asked if the items were clear to understand. The acceptability, clarity, and understandability of the translated version were evaluated. A final review of the questionnaire was produced by the authors and approved by the author of the original questionnaire. RESULTS: Some idiomatic, semantic, and experiential inconsistencies were identified and properly adjusted. Item 3 was considered the most unclear item (23,3%). Items 7, 8, and 9 presented clarity above 80% (93%, 90%, and 90%, respectively). Suggestions were discussed and incorporated into the tool and COLA was found to be clear and easy to understand. CONCLUSIONS: The Brazilian version of the COLA was easily understood by healthcare professionals and adapted to Brazilian culture. Translation and cultural adaptation of the COLA instrument into Brazilian Portuguese can be an important case-finding instrument for chronic obstructive pulmonary disease in Brazil.